Implementasi Customer Relationship Management (CRM) pada Sistem Informasi Pemasaran dengan Menggunakan Framework React.JS Berbasis Website - Fauzan Muhammad; Iskandar Fitri; Rini Nuraini (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2022)
Life in the current era of technology is almost every line connected to the internet, as well as when doing business. Website is a container used for business development and improvement. One form of this is to create an attractive website display as a strategy to increase product quality and quantity. This research aims to; 1) The creation of a marketing information system facility with the application of CRM using the web-based React.JS framework as the main purpose of the research, and 2) Understanding and describing the benefits of implementing a Marketing Information System with CRM Applications using the web-based React.JS framework as a marketing strategy to improve quality and product quantity. To implement this research, the researcher uses the Agile method. A website-based marketing system with the implementation of Customer Relationship Management (CRM) at Reswara Digital printing produces structured and detailed data storage and the delivery of product information to consumers can be carried out optimally.